How blind is the watchmaker? : nature's design & the limits of naturalistic science - Broom, Neil, 1945- (Downers Grove, Ill. : InterVarsity Press, 2001)
"If you found a watch, as William Paley asked nearly two centuries ago, would you think that it came into existence by chance or that there was a watchmaker? Likewise, Neil Broom asks, was the universe created by the blind forces of nature, or is there evidence of a designing mind?" "While prominent scientists in recent years have suggested that the watchmaker is indeed blind, Broom sees much more than their naturalistic blinders allow them to perceive. This book, written by a biomechanics scientist, boldly challenges the scientific establishment's commitment to what he labels as "the flimsily crafted but persuasively packaged myth of scientific materialism." "The author reveals how naturalistic science is guilty of attempting to reduce all explanations to the molecular level, even when higher nonmaterial levels of explanation are clearly required to describe the behavior of many systems. Likewise he shows why there is little chance that science can define life in a way that seamlessly connects it to the inanimate world."--BOOK JACKET
New shape of "divinity" -- Business of science -- What is life? -- Birth of life: popular view -- Serious science & life's origin -- Trade secrets of origin-of-life science -- Games of chance & the evolution of life -- New-Darwinism: crown jewel of materialistic science -- New-Darwinism's struggle to survive -- How natural is natural selection? -- Biology & destiny -- Beyond naturalism
New Zealand author
"Foreword by William A. Dembski"--Cover
Previous ed.: Aldershot : Ashgate Pub., 1998
Includes bibliographical references and index
Keywords: Science -- Philosophy; Science -- Social aspects; Life -- Origin -- Philosophy; Materialism; Religion and science